2022
DOI: 10.1007/s00421-021-04870-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma potassium concentration and cardiac repolarisation markers, Tpeak–Tend and Tpeak–Tend/QT, during and after exercise in healthy participants and in end-stage renal disease

Abstract: The cardiac T-wave peak-to-end interval (Tpe) is thought to reflect dispersion in ventricular repolarisation, with abnormalities in Tpe associated with increased risk of arrhythmia. Extracellular K + modulates cardiac repolarisation and since arterial plasma K + concentration ([K + ]) rapidly increases during and declines following exercise, we investigated the relationship between [K + ] and Tpe with exercise. MethodsSerial ECGs (Tpe, Tpe/QT ratio) and [K + ] were obtained from 8 healthy, normokalaemic volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…No studies have detailed [K + ] dynamics in elite rowers to ascertain whether greater K + shifts are elicited. Prolongation of the cardiac QT interval and T wave peak-to-end interval after exercise were related to [K + ] a , suggesting the possibility of vulnerability to arrhythmias (Atanasovska et al 2018 ; Tran et al 2022 ). In contrast to rowing, cross country skiing, for traditional events, is usually for much longer duration and at a lower intensity, with only modest [K + ] found “immediately after” skiing, although the timing of sampling is unclear.…”
Section: Plasma [K + ] During and Following Exerci...mentioning
confidence: 99%
“…No studies have detailed [K + ] dynamics in elite rowers to ascertain whether greater K + shifts are elicited. Prolongation of the cardiac QT interval and T wave peak-to-end interval after exercise were related to [K + ] a , suggesting the possibility of vulnerability to arrhythmias (Atanasovska et al 2018 ; Tran et al 2022 ). In contrast to rowing, cross country skiing, for traditional events, is usually for much longer duration and at a lower intensity, with only modest [K + ] found “immediately after” skiing, although the timing of sampling is unclear.…”
Section: Plasma [K + ] During and Following Exerci...mentioning
confidence: 99%
“…Adaptive control is driven by circadian rhythm [1] . In addition, some studies have focused on the effect of the external environment on serum potassium concentrations and found that age, sex, exercise, diet, and occupation could play a role [2] , [3] , [4] , for example, the male sex and administrative occupations were associated with a higher potassium intake [5] . Moreover, serum potassium concentrations show continuous and parallel decreases with age in both sexes, which may be related to physiological aging [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%
“…During intense cycling, running or rowing, [K + ] in arterial plasma reaches 6−8 mmol l −1 and even higher in femoral venous plasma; this is followed by rapid post‐exercise reductions in [K + ], often to sub‐resting values or even hypokalaemia (Atanasovska et al., 2014, 2018; Lindinger et al., 1992; McKenna, Heigenhauser, McKelvie, MacDougall et al., 1997; Medbo & Sejersted, 1990; Vollestad et al., 1994). Post‐exercise hypokalaemia is also associated with impaired cardiac repolarisation and increased risk of arrhythmias (Atanasovska et al., 2018; Lindinger & Cairns, 2021; Tran et al., 2022). Hence, K + regulation is critical both during and after exercise.…”
Section: Introductionmentioning
confidence: 99%